Emawa dan Owaada Suku Mee – Spirit Memanggil Kembali Sebuah Refleksi Teologis tentangKoinonia - Rynanta, Reinardus Bhadar Agastya; Loi, Angelinus; Sawa, Yohanes Don Bosco (Perspektif, 2020)
The Mee tribe in Papua has an emawa owaada philosophy of life. These two words (emawa meaning house; owaada meaning garden, field) have a living symbolic meaning. Emawa is defined as the house of truth, a place for people to get education, build relationships with others, and be grateful for life. Owaada is a symbol of mother who gives life. In this article the authors try to reflect on the philosophy of emawa owaada in the light of Christian theology, especially the theology of koinonia (communion) which culminates in the celebration of the holy Eucharist. As the Mee people are ‘called home’ to warm themselves, dialogue, exchange ideas, share life and give thanks to Ugamate (the Holy One), so the Church invites people to come together in communion to share life and give thanks to the Almighty and Living God. The authors argue that the path to true inculturation is still a long way to go, but the possibility is very open.